1979
DOI: 10.1104/pp.63.6.1165
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate Levels and Photoassimilate Export from Leaves of Phaseolus vulgaris Exposed to Excess Cobalt, Nickel, and Zinc

Abstract: Exposure of white bean seedlings to phytotoxic burdens of Co, Ni, or Zn reduced the export of "C-photoassimilates from the nearly fully expanded unifoliate leaves. Little "C reached the major sink areas, the young trifoliate leaves and the root tips, of seedngs exposed to metal. The unifoliate leaves accumulated sucrose, reducing sugars, and starch. These effects were evident within 1 or 2 days.The most general symptoms of metal toxicity in plants are stunting and chlorosis (7). Yield reductions could occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
36
0
2

Year Published

1979
1979
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(42 citation statements)
references
References 15 publications
4
36
0
2
Order By: Relevance
“…The low content of soluble carbohydrate suggested that plants consumed a large amount of soluble sugar to maintain the basic physiological functions, such as photosynthesis and respiration. Our results were in agreement with the report of Samarakoon and Rauser (1979) that converse changes of carbohydrate and photosynthesis in leaves of Phaseolus vulgaris under excess Ni stress.…”
Section: Discussionsupporting
confidence: 94%
“…The low content of soluble carbohydrate suggested that plants consumed a large amount of soluble sugar to maintain the basic physiological functions, such as photosynthesis and respiration. Our results were in agreement with the report of Samarakoon and Rauser (1979) that converse changes of carbohydrate and photosynthesis in leaves of Phaseolus vulgaris under excess Ni stress.…”
Section: Discussionsupporting
confidence: 94%
“…The results are consistent with the results of Aly and Mohamed [29], who observed an enhancement in total sugars in Zea mays under Cu(II) stress, and with Samarakoon and Rauser [30] who found that reducing sugars increased in Phaseolus vulgaris plants under Ni and Zn stress. Sugars play role in osmoregulation and act as storage reserves to support the basal metabolism of plants under stress [31].…”
Section: Discussionsupporting
confidence: 82%
“…Agarwala et al (1977) também observaram que o excesso de Zn 2+ reduz a translocação de Fe em cevada, sem, entretanto, isto estar relacionado com a ação induzida do Zn. É sabido que o excesso de Zn pode interferir no metabolismo de carboidratos, inibindo o transporte de fotoassimilados (Samarakoon & Rauser, 1979), e afetando o crescimento da planta.…”
Section: Resultsunclassified